Geografia das colônias agrícolas no médio rio Amazonas, município de Urucará-AM - Arenilton Monteiro Serrão; Manuel de Jesus Masulo da Cruz (Confins)
The social subjects in which we deal in this research, the settlers, peasants historically constituted in the floodplains of the middle Amazon River, especially in the municipalities of Urucará, Parintins and Urucurituba. In this ecosystem, through the absorption of different cultural traits, they established economic, social and territorial relations, a condition that prevailed until the mid 1950s, when large floods / floods and land unavailability forced permanent migration to land areas in the 1960/70. Historically the base of socioeconomic support of these municipalities, in particular Urucará, the focus of our research, was linked to peasant activity and its possible relations with land, forest and water made possible subsistence agriculture, extractive practices and fishing activities, highlighting the várzea in life and established relationships. Its mercantile integration made possible the exchange of products and merchandise and at the same time, relations of exploitation and subordination of peasant labor, a system broken or accentuated by the new political, economic and social conjunctures of the 1960s. This decade is emblematic not only by the visibility that the social movements in the countryside acquired in Brazil, but especially by the organization and strengthening of the peasantry in the middle Amazon River. Peasant territorialization on the mainland took place through Ecclesiastical Communities of Bases and agricultural colonies, strengthening their struggles through the creation of entities (associations, cooperatives, unions, School Family Agriculture) and mainly, of an institution that coordinates and articulates the actions together to the state sectors, engaged in one way or another, to awaken the political and social consciousness of these social subjects.